Development of Zn1−xBaxO nanoparticles reinforced poly(vinyl alcohol) macromolecular nanocomposite films: Eco‐friendly integrated materials for optical systems. Issue 34 (19th July 2022) - Chandrappa, Halli; Bhajantri, Rajashekhar Fakeerappa; Ismayil; Ganesha, Kaliyur Nanjundaiah
Abstract: In this paper, we report the synthesis of Ba doped ZnO (Zn1−x Bax O, [ x = 0.05]) nanoparticles (NPs) with a polycrystalline hexagonal wurtzite structure using chemical co‐precipitation method and prepared optically transparent, high refractive index polymer nanocomposite films by incorporating Zn1−x Bax O into poly(vinyl alcohol) (PVA) matrix. The average crystallite size of 104 nm was estimated by Scherrer's formula from X‐ray diffraction (XRD) patterns. The crystallinity of the composite film is significantly increased when Zn1−x Bax O NPs are added. The basic principles and theoretical aspects of scattering, transparency and refractive index of the composite structures are discussed. The formation of ZnBaO inter metallic bond was confirmed by the IR peaks that appear at the spectral wavenumbers (⁓596–608) cm −1 . ATR‐FTIR spectral transmittance strongly proves the intermolecular interactions that occur in the composite film with molecular modification and various functional group impressions. UV–Vis absorption spectrum demonstrates a strong absorption edge around 379 nm owing to oxygen species corresponding to ZnBaO nanostructures in the composite films. The developed polymer composite films yielded strikingly higher RI value of ⁓( n = 2.5) having Abbe's number ( υ D = 10) with 57% plus transparency for 5 wt% NPs (ZBP‐3) with sufficiently low extinction coefficient values ( k ⁓10 −4 ). Optical conductivity ( σ opt ) was found to elevate from σ opt ⁓ (4.465 × 10 10 ) s −1 for pristine PVA to a σ opt ⁓ (1.309 × 10 12 ) s −1 for 5 wt% Zn0.95 Ba0.05 O filled composite films. Differential scanning calorimetry analysis showed a significant increase in the T g value. The significant increase in T m and T d > 311°C values indicates excellent thermal stability. Hence, the nanocomposite films demonstrated an integrated system of excellent refractive index, considerable visual transparency and excellent thermal stability, establishing their potential for use as a wider spectrum of optical system requirements. Abstract : Integrated Polymer Nanocomposites for Optical Applications